2015
DOI: 10.9788/tp2015.3-20
|View full text |Cite
|
Sign up to set email alerts
|

Percepções do homossexual masculino: sociedade, família e amizades

Abstract: ResumoO objetivo deste estudo foi compreender as percepções do homossexual masculino sobre a sua orientação sexual e as possíveis repercussões da sua homossexualidade no contexto familiar e social onde vive. Trata-se de uma pesquisa qualitativa com delineamento exploratório e descritivo. Os dados foram coletados por meio de entrevista semiestruturada contendo questões norteadoras focando os sentimentos, os comportamentos e as percepções dos participantes sobre sua homossexualidade e sobre as relações com famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
0
5
0
10
Order By: Relevance
“…Reinforcing the idea of discrimination in the family nucleus and contradicting the study of Costa et al (2015), Palma and Levandowski (2008) found, during interviews with lesbian women, the perception that family members reacted negatively to the coming out process. There were improvement in the posture after some time in some cases, while in others, the fathers and mothers still did not accept the daughter's homosexuality, which is somewhat similar to the reality experienced by many men interviewed in other studies (Cadieux & Chasteen, 2015;Guardarrama & Alfonso, 2012).…”
Section: Homosexuality and Family: Outness And The Coming Out Processmentioning
confidence: 84%
See 3 more Smart Citations
“…Reinforcing the idea of discrimination in the family nucleus and contradicting the study of Costa et al (2015), Palma and Levandowski (2008) found, during interviews with lesbian women, the perception that family members reacted negatively to the coming out process. There were improvement in the posture after some time in some cases, while in others, the fathers and mothers still did not accept the daughter's homosexuality, which is somewhat similar to the reality experienced by many men interviewed in other studies (Cadieux & Chasteen, 2015;Guardarrama & Alfonso, 2012).…”
Section: Homosexuality and Family: Outness And The Coming Out Processmentioning
confidence: 84%
“…The family was also seen as fundamental for the subjects to feel encouraged and supported to reveal their sexual orientation, which also provided strength for them to reveal themselves in the workplace and in other places outside his home (Palma, Piason, Bezerra, & Strey, 2010;Sabat, Trump, & King, 2014). It can be observed that with the male population the discourse is not always the same, with discrimination being more noticeable in the statements analyzed, which may also be related to gender issues (Costa et al, 2015;Simpson, Miranda, Mundo, & Azevedo 2007).…”
Section: Homosexuality and Family: Outness And The Coming Out Processmentioning
confidence: 99%
See 2 more Smart Citations
“…A partir desses estudos (Costa et al, 2015;Guardarrama & Alfonso, 2012), nota-se que, se houvessem mais discussões e informações acerca da homossexualidade, a possibilidade da quebra de paradigmas e preconceitos poderia ocorrer, de modo que tanto os homossexuais quanto suas famílias pudessem passar pelo processo de aceitação de forma menos dolorosa. Vale refl etir, ainda, acerca da expectativa e da realidade vividas pelos(as) homossexuais que optam pelo processo de coming out, mesmo que seletivo, a fi m de que possam buscar apoio em amigos ou instituições que os acolham, de fato, sem preconceitos.…”
Section: Homossexualidade E Família: Outness E O Processo De Coming Outunclassified